2016
DOI: 10.1177/0309324715614759
|View full text |Cite
|
Sign up to set email alerts
|

Integrated digital image correlation applied to elastoplastic identification in a biaxial experiment

Abstract: The identification of the parameters of several constitutive laws is performed with the Integrated Digital Image Correlation (IDIC) technique in a biaxial experiment for a cruciform specimen made of stainless steel. The sought material parameters are assessed with the contribution of both reaction forces (from load sensors) and displacement fields (measured via digital image correlation). For each constitutive law a global residual quantifying the model error is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Instead of having the same amplitude on the longitudinal and transverse components, it is proposed to look for three different amplitudes α x , α y and α z for each direction. Before performing the identification, a sensitivity analysis is carried out [81]. It consists in computing the dimensionless static Hessian for a given variation of the sought parameters (here chosen equal to 10%)…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Instead of having the same amplitude on the longitudinal and transverse components, it is proposed to look for three different amplitudes α x , α y and α z for each direction. Before performing the identification, a sensitivity analysis is carried out [81]. It consists in computing the dimensionless static Hessian for a given variation of the sought parameters (here chosen equal to 10%)…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Finite element model updating was performed to calibrate anisotropic plasticity parameters . It was also shown that integrated digital image correlation could be used to tune von Mises plasticity parameters on such type of samples. This technique will be used herein to investigate plastic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, a single experiment on an ultrathin biaxial specimen is performed, and four constitutive laws with increasing complexity are considered to challenge the sought behavior. To enhance the relevance of the model, all data (i.e., displacement fields and reaction forces) are equitably weighted via a Bayesian foundation …”
Section: Introductionmentioning
confidence: 99%
“…The constrained registration is then limited to the sensitivity fields (ie, variation of the displacement field with respect to unknown parameters of the model) provided by either closed‐form solutions() or FE predictions. ()…”
Section: Introductionmentioning
confidence: 99%